A Robust Method for Perfusable Microvascular Network Formation In Vitro. Issue 6 (3rd April 2022) - Wan, Zhengpeng; Zhong, Amy X.; Zhang, Shun; Pavlou, Georgios; Coughlin, Mark F.; Shelton, Sarah E.; Nguyen, Huu Tuan; Lorch, Jochen H.; Barbie, David A.; Kamm, Roger D.
Abstract: Micropost‐based microfluidic devices are widely used for microvascular network (MVN) formation in diverse research fields. However, consistently generating perfusable MVNs of physiological morphology and dimension has proven to be challenging. Here, how initial seeding parameters determine key characteristics of MVN formation is investigated and a robust two‐step seeding strategy to generate perfusable physiological MVNs in microfluidic devices is established. Abstract : Microvascular network (MVN) generated in microfluidic devices are widely used in diverse research fields. But, forming perfusable MVNs with physiological diameters has proven to be challenging. In this study, seeding parameters that control MVN geometry are explored and a robust two‐step seeding method to form perfusable physiological MVNs with various vascular cells is established.